Disgusting politics: circuits of affects and the making of Bolsonaro. Issue 5 (20th October 2021) - Borba, Rodrigo
ABSTRACT: Jair Bolsonaro, the unapologetically homophobic and ultraconservative Brazilian president, managed to emerge from the margins of the political system and gained electoral momentum during the impeachment hearing against Dilma Rousseff in 2016. The hearing, which ultimately demoted the first female president of the country, epitomizes the current affective polarization of Brazil in which sexual dissidence plays an important role. This paper discusses the politics of discourse, affect and sexuality which has drawn Bolsonaro and his far-right ideologies into greater political relief. To do so, I will focus on the scene in which Jean Wyllys, a human rights activist and the only openly gay congressmember at the time, spat on Bolsonaro. Wyllys' misdemeanor caused a commotion in the country and was recontextualized in several venues such as memes, social media, op-eds, YouTube parodies etc. This paper investigates the intense circulation of Wyllys' actions and how it responds to and takes issue with the larger affective scenario of the country. I analyze the socio-semiotic life of Wyllys' spit by tracking its textual trajectory with a view to discussing the performativity of disgust and the forging of political (in)sensibilities with regards to gender and sexuality in contemporary Brazil.